2011
DOI: 10.1590/s1516-18462011005000141
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de crianças e adolescentes em tarefas envolvendo habilidade auditiva de ordenação temporal simples

Abstract: RESUMOObjetivo: analisar o desempenho de crianças e adolescentes na habilidade auditiva de ordenação temporal simples segundo as variáveis: idade, sexo, queixas e hipóteses diagnósticas fonoaudioló-gicas. Método: trata-se de 400 sujeitos, na faixa etária de 4 e 14 anos, avaliados no período 2006 a julho de 2010. Os instrumentos de coleta de dados foram anamnese e os testes de sequencialização de sons verbais (MSV) e não-verbais (MSNV). Para análise dos dados foi utilizado o programa SPSS versão 12, cálculo do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 15 publications
4
11
0
2
Order By: Relevance
“…This finding corroborates other studies that show that children with learning difficulties present changes in their temporal auditory processing (6,11,(20)(21)(22) . Parents reported a high number of behavioral manifestations, such as hyperactivity/inattention, conduct problems, peer relationship problems, and emotional symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding corroborates other studies that show that children with learning difficulties present changes in their temporal auditory processing (6,11,(20)(21)(22) . Parents reported a high number of behavioral manifestations, such as hyperactivity/inattention, conduct problems, peer relationship problems, and emotional symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…This finding corroborates the literature, which shows articles reporting improved performance in the NVSSMT and VWMT for children aged four to 14 years (22) , as well as in temporal resolution (21) . The processing of information is dependent on the neural function and must be interpreted within the context of neuromaturation.…”
Section: Discussionsupporting
confidence: 92%
“…The relationship between age and performance of the children in the auditory processing showed that children aged 5 years showed more adequacy, result justified by the fact that the hearing abilities improve over time, associated with the time of exposition to sound stimulus (19,20) . In this study, the comparison between gender and auditory processing revealed no statistical significance.…”
Section: Discussionmentioning
confidence: 97%
“…Esse ruído pode afetar a comunicação em sala de aula e o aprendizado conforme discutido por Knecht et al, 2002;Dreossi, Momensohn-Santos, 2005;Aroszewski et al, 2007 em seus estudos sobre as alterações que podem ocorrer aos estudantes de uma escola que estão sob impacto de ruídos internos ou externos às suas instalações. Ainda, os ruídos podem prejudicar a habilidade de atenção auditiva do escolar podendo levar a dificuldades em escrever, ler, manter atenção e concentração (Lacerda e Marasca, 2001;Eniz, 2004 (Share, 2002;Engelmann e Ferreira, 2009;Dias et al, 2011;Mourão et al, 2012;Chaubet et al, 2014;Steinbrink et al, 2014).…”
Section: Efeito Do Ta Nas Medidas Comportamentais Do Processamento Auunclassified